Gender role in galician traditional music: From tradition to the present: analysis and didactic possibilities - López Fernández, Carme (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this article we work within the field of traditional music, linking it with the gender perspective through the analysis of the roles established both in tradition and today. To do this, we establish a methodology based on conducting interviews as a means to make up for the lack of bibliographical references. Our results focus on the continuity of gender roles and their distribution through power relations, regardless of the changes in context that have occurred between tradition and the present. Finally we will reflect the current interest and the didactic possibilities on the subject.